Turbine sealing steam heat recovery with dynamic Stirling engines - Strušnik, Dušan (JET on-line, 2014)
This paper presents the possibilities of sealing steam heat recovery in a steam condensation turbine with the use of dynamic Stirling engines. The installation of dynamic Stirling engines into the turbine sealing steam system allows the recovery of sealing steam heat and the generation of electrical energy. The Stirling engine dynamics are expressed with a built-in working gas storage tank and working gas flow control to ensure adequate power output of the Stirling engine. The working gas quantity in the engine is controlled with regard to the available turbine sealing steam heat. Via the measurement of the turbine sealing steam quantity and quality, a model of the working gas pressure conditions in the Stirling engine is designed. The engine responsiveness at various working gas quantities and types is analysed.
Keywords: analysis; efficiency; energetika; heat; isochoric compression; izkoristek toplote; para; parne turbine; pogonska para; regenerator; sealing steam; steam turbine; Stirling engine; Stirlingov motor; working gas